Pengaruh Kualitas Komite Audit, Workload Dan Rotasi Auditor Terhadap Kualitas Audit - Nada Pertiwi; Erinos NR (Jurnal Eksplorasi Akuntansi, 2020)
This study aims to determine the effect of audit committee quality, workload, audit rotation on audit quality in financial companies listed on the Indonesia Stock Exchange (idx) for the period 2016-2018. This research is a causative research. The population in this study are financial companies listed on the Indonesia Stock Exchange (BEI) for the period 2016-2018. By using purposive sampling method, obtained 107 companies as research samples. The type of data used is secondary data and multiple regression analysis is used. The results of this study indicate that the quality of the audit committee and audit rotation do not have a significant effect on financial quality, only workload has a significant effect on the financial statements